Pengaruh Modal Kerja Terhadap Profitabilitas dan Nilai Perusahaan - Nafisah, Durotun; Nirawati, Lia; Samsudin, Acep; Rijali, Fitri Auliya; Wijaya, Angela Clarisa; Fitria, Diana Azizatul; Hadir, Oktaviani Arcici; Syachruddin, Anisah Inas (CV. Lafadz Jaya, 2022)
There are so many things that will be needed by a company to realize its goals, including working capital. The existence of working capital itself is so essential for a company because a company requires working capital in carrying out its operational activities. This study aims to determine the effect of working capital on profitability and firm value. The method used in this research is the literature study method. Researchers collect reference sources from several journals and books by selecting, comparing, merging, and sorting so that relevant compilations are obtained. The results of the study state that working capital management is needed by a company in order to achieve and grow profitability and good working capital management can have a positive influence on firm value.